Normal breast tissue stiffness measured by a new ultrasound technique: virtual touch tissue imaging quantification (VTIQ) - Golatta, Michael; Schweitzer-Martin, Mirjam; Harcos, Aba; Schott, Sarah; Junkermann, Hans; Rauch, Geraldine; Sohn, Christof; Heil, Jörg (European journal of radiology, 2013)
Objective - To evaluate normal breast tissue stiffness with virtual touch tissue imaging quantification (VTIQ) using prospectively collected data. - Materials and Methods - B-mode ultrasound and VTIQ were performed in 132 breasts in 97 women. Mean values of VTIQ for parenchyma and fatty tissue were compared between those measured in healthy breasts and in the surrounding of histologically proven benign and malignant breast lesions. Moreover we reviewed VTIQ values according to breast density measured by the American College of Radiology (ACR) categories. In addition we analyzed re-test reliability of VTIQ. - Results - In 132 breasts the mean VTIQ values in parenchyma were significantly higher than in fatty tissue (3.23m/s±0.74 versus 2.5m/s±0.61; p<0.0001). In healthy breasts as well as in the surrounding of a benign or malignant lesions the VTIQ values of parenchyma were similar (p=0.12). In fatty tissue, small differences between mean VTIQ values of 2.25m/s±0.51, 2.52m/s±0.48 and 2.65m/s±0.71 (p=0.01) in the respective groups were observed. The comparison of mean VTIQ values of parenchyma and fatty tissue in more and less dense breasts (ACR 1+2 versus ACR 3+4 breasts) also yielded no statistically significant difference. The re-test reliability of VTIQ assessed with three independent measurements was moderate (interclass-correlation of 0.52 (p<0.0001)). - Conclusion - VTIQ is a reliable method for measuring the stiffness of breast tissue. We propose standard values for healthy parenchyma and fatty tissues independent of the surrounding tissue or the ACR category.
Gesehen am 17.02.2020